Role of hepatitis B surface antigen in hepatitis B virus relapse after entecavir or tenofovir prophylaxis in patients undergoing cancer chemotherapy. Issue 10 (17th April 2018) - Kuo, Ming‐Te; Tseng, Po‐Lin; Chou, Yeh‐Pin; Chang, Kuo‐Chin; Tsai, Ming‐Chao; Kuo, Yuan‐Hung; Hu, Tsung‐Hui; Hung, Chao‐Hung; Wang, Jing‐Houng; Lu, Sheng‐Nan; Chen, Chien‐Hung
Abstract: Background and Aim: This study investigated whether hepatitis B surface antigen (HBsAg) could predict hepatitis B virus (HBV) relapse after cessation of entecavir or tenofovir disoproxil fumarate (TDF) prophylaxis for chronic hepatitis B cancer patients who are undergoing chemotherapy. Methods: The study enrolled 122 hepatitis B e‐antigen‐negative cancer patients who underwent chemotherapy with entecavir or TDF for antiviral prophylaxis and posttreatment follow‐up for at least 6 months. Results: Of the 122 patients, 52 and 18 experienced virological and clinical relapse, which had 3‐year cumulative incidences of 46.6% and 18.6%, respectively. Multivariate analysis showed that end‐of‐treatment HBsAg levels and baseline HBV‐DNA ≥ 2000 IU/mL were independent predictors of virological relapse. The best HBsAg cutoff value was 500 IU/mL. An end‐of‐treatment HBsAg of 500 IU/mL was useful for predicting virological relapse in patients with baseline HBV‐DNA < 2000 IU/mL (3‐year rate: 21.3% vs 46.4%, P = 0.038, in patients with HBsAg < 500 and ≥ 500 IU/mL, respectively), but not in patients with baseline HBV‐DNA ≥ 2000 IU/mL. Of the 52 patients who experienced virological relapse, 13 experienced transient virological relapse. Patients with baseline HBV‐DNA level < 2000 IU/mL experienced a higher rate of transient virological relapse (42.1% vs 15.2%, P = 0.031). Three patients experienced hepatic decompensation upon alanine aminotransferase flares, and no patient died after timely retreatment. Ten patients experienced posttreatment HBsAg loss, and the 3‐year HBsAg loss rate was 30.7% in patients with end‐of‐treatment HBsAg < 100 IU/mL. Conclusions: The baseline HBV‐DNA and end‐of‐treatment HBsAg levels could predict virological relapse after withdrawal of entecavir and TDF prophylaxis for chemotherapy.